Edukasi TP PKK dan Tokoh Masyarakat dalam Pencegahan Demam Berdarah - Nurwahidah; Ahmad, Ahmad; Imam Fadhlullah P; Annisa Dwi kemalahayati; M Fahrurrahman; St. Mifta Hayatun (CV. CENDIKIA JENIUS INDONESIA, 2025)
Dengue Hemorrhagic Fever (DHF) is caused by the dengue virus, transmitted through the bite of the Aedes aegypti mosquito. This disease is a serious concern in tropical regions such as Indonesia. This community service aims to analyze the improvement of health cadres' knowledge and skills through education by TP PKK and community leaders in DHF prevention in Nggembe Village, Bolo District, Bima Regency. The methods used include lectures, discussions, demonstrations, and the creation of educational materials such as leaflets and banners. The activities took place on November 4, 11, and 18, 2024, involving preparation, implementation, monitoring, and evaluation. Results show that most cadres are aged 24-35 years, predominantly female, and have a high school education. Before the intervention, 70% had low knowledge, which improved to 90% in the good category after the intervention. Skills also improved from 56% low to 80% good. Education by TP PKK and community leaders effectively enhanced health cadres' capacity. In conclusion, a structured and participatory educational approach strengthens cadres' roles as agents of change in DHF prevention, with continuous evaluation ensuring program sustainability.